Shape-memory properties of crosslinked biobased polyurethanes. (May 2016) - Calvo-Correas, Tamara; Gabilondo, Nagore; Alonso-Varona, Ana; Palomares, Teodoro; Corcuera, M. Angeles; Eceiza, Arantxa
Graphical abstract: Highlights: Thermally-responsive crosslinked biobased polyurethanes were synthesized successfully. The macrodiol and the diisocyanate used were derived from renewable sources. Shape-memory varied with crosslink density and maximum elongation. Preliminary in vitro cytotoxicity assays showed non-toxic behavior. Abstract: Biobased crosslinked polyurethanes were synthesized and characterized as shape-memory polymers. Both the macrodiol and the diisocyanate were derived from renewable sources; the first one from castor oil, and the second one froml -lysine amino acid. The influence of component molar ratios, crosslink density and maximum elongation on the shape-memory properties was analyzed. The thermal analysis showed that polyurethanes were microphase separated. Though the study of the shape-memory properties, it was seen that shape-memory was influenced by crosslink density. A higher crosslink density led to a greater shape recovery, since crosslinks are the responsible for memorizing the shape of the material. With the increase of maximum elongation, both shape fixity and recovery decreased due to higher amount of crosslink net points were broken. Moreover, the synthesized polyurethanes showed its potential to be used in biomedical applications, according to the preliminary in vitro cytotoxicity assays.